A Multidimensional Interface and Nigerian Political Discourse: A Case Study of Ideological Issues Underlying Coronavirus Discourse in Nigeria. Issue 1 (2nd January 2022) - Akinlotan, Mayowa
Abstract: This article proposes a theoretical framework modelling the Nigerian socio-political landscape through coronavirus news headlines. Drawing on news headlines from major newspapers in Nigeria reporting on the coronavirus pandemic, the article argues that discourses in Nigeria can gain significant insights through the analytic lens of a multidimensional interface. The principle argues that certain multidimensional ideologies are universal to discourses in Nigeria, including all of its participants, the social structure, and all that makes up these structures. It is also argued that a meaningful interpretation and analysis of socio-political texts in Nigeria is only possible through the conceptual elements identified in the proposed model.